Dietary Heme Induces Gut Dysbiosis, Aggravates Colitis, and Potentiates the Development of Adenomas in Mice - Constante, Marco; Fragoso, Gabriela; Calvé, Annie; Samba-Mondonga, Macha; Santos, Manuela M. (Frontiers in Microbiology, 2017)
Dietary heme can be used by colonic bacteria equipped with heme-uptake systems as a growth factor and thereby impact on the microbial community structure. The impact of heme on the gut microbiota composition may be particularly pertinent in chronic inflammation such as in inflammatory bowel disease (IBD), where a strong association with gut dysbiosis has been consistently reported. In this study we investigated the influence of dietary heme on the gut microbiota and inferred metagenomic composition, and on chemically-induced colitis and colitis-associated adenoma development in mice. Using 16S rRNA gene sequencing, we found that mice fed a diet supplemented with heme significantly altered their microbiota composition, characterized by a decrease in -diversity, a reduction of Firmicutes and an increase of Proteobacteria, particularly Enterobacteriaceae. These changes where similar to shifts seen in dextran sodium sulfate (DSS) -treated mice to induce colitis. In addition, dietary heme contributed to the exacerbation of DSS-induced colitis and facilitated adenoma formation in the Azoxymethane/DSS colorectal mouse model. Using inferred metagenomics (PICRUSt), we found that the microbiota alterations elicited by dietary heme resulted in non-beneficial functional shifts, which were also characteristic of DSS-induced colitis. Furthermore, a reduction in fecal butyrate was found in mice fed the heme supplemented diet compared to mice fed the standard diet. Iron metabolism genes known to contribute to heme release from red blood cells, heme uptake, and heme exporter proteins, were significantly enriched, indicating a shift towards favouring the growth of bacteria able to uptake heme and protect against its toxicity. In conclusion, our data suggest that luminal heme, originating from dietary components or gastrointestinal bleeding in IBD and, to lesser extent in CRC, directly contributes to microbiota dysbiosis. Thus, luminal heme levels may further exacerbate colitis through the modulation of the gut microbiota and its metagenomic functional composition. Our data may have implications in the development of novel targets for therapeutic intervention aimed at lowering gastrointestinal heme levels through heme chelation or degradation using probiotics and nutritional interventions.